2018
DOI: 10.1155/2018/8252570
|View full text |Cite
|
Sign up to set email alerts
|

Using MR-FTIR and Texture Profile to Track the Effect of Storage Time and Temperature on Pita Bread Staling

Abstract: Textural deterioration of pita bread, PB, due to staling is an important quality parameter during storage. Loss of freshness due to PB staling results in significant quality and economic loss. PB staling was studied using both MR-FTIR spectroscopy and textural profile including time to rupture and tensile and compressive forces. The study was conducted at room temperature (23°C) and freezing temperature (−18°C) over 96 h of storage time after baking. Some physical properties of PB such as loaf weight, dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
(36 reference statements)
1
6
0
Order By: Relevance
“…With regard to flat bread tensile tests and near-infrared reflectance spectroscopy were used to monitor flat bread ageing treated by preservatives. Al-Mahsaneh et al (2018) reported high R 2 values and confirmed that the NIRS along with texture analysis are valuable tools to detect the effect of the preservatives on shelf-life and quality of flat bread.…”
Section: Nir Spectroscopysupporting
confidence: 53%
“…With regard to flat bread tensile tests and near-infrared reflectance spectroscopy were used to monitor flat bread ageing treated by preservatives. Al-Mahsaneh et al (2018) reported high R 2 values and confirmed that the NIRS along with texture analysis are valuable tools to detect the effect of the preservatives on shelf-life and quality of flat bread.…”
Section: Nir Spectroscopysupporting
confidence: 53%
“…The peaks expressed on Day 90 were slightly higher intensity than those of Day 0 especially at 1,074/992 and 3,284 cm −1 assigned to the crystalline/amorphous regions of starch and O-H bond stretching, respectively. According to Al-Mahsaneh et al (2018), unit absorbance increased with storage time in the band 900-1150 cm −1 , which corresponds to the "saccharides" group indicating progressive starch crystallization with storage time due to starch retrogradation.…”
Section: Ft-ir Spectroscopymentioning
confidence: 99%
“…It is observed the -OH bond 3000-3600 cm −1 corresponds to the stretching vibration band and the 900-1150 cm −1 bands, which correspond to the saccharides group. Al-Mahsaneh et al [19] reported that these groups increase during the storage time based on their absorbance study. The −OH group is associated with the effect of water mobility on waterstarch-protein interaction.…”
Section: Resultsmentioning
confidence: 99%